Rancang Bangun Sistem Pakar Untuk Mendiagnosa Penyakit Dispepsia Dengan Metode Forward Chaining - Yasinta istiqomah; Joni Maulindar; Dwi Hartanti (Infotek: Jurnal Informatika dan Teknologi, 2023)
Dyspepsia is a digestive disorder that causes discomfort or pain in the stomach. In expert systems, the forward chaining method is used to diagnose this disease. This method evaluates the facts or symptoms obtained from the patient, then determines the appropriate diagnosis. The application of the forward chaining method in an expert system allows for an efficient and systematic evaluation of patient symptoms, so that patients can make their own detections and can make further decisions so that their disease can be treated immediately. This technology-based approach enhances the diagnostic process and facilitates rapid intervention. The expert system developed to diagnose dyspepsia has been successfully implemented using knowledge that includes 21 symptoms and 3 types of related diseases. System validation was carried out by testing 30 data samples, and the results showed that the system has an accuracy rate of up to 90% in correctly identifying and diagnosing dyspepsia. This shows that the expert system has a high level of expertise in analyzing the symptoms presented and providing a reliable diagnosis